2007
DOI: 10.1186/1741-7015-5-3
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for placebo effects on physical but not on biochemical outcome parameters: a review of clinical trials

Abstract: Background: Recent reviews on placebo effects in clinical trials suggest that objective changes following placebo treatments may not exist or, at least, have been considerably overestimated. However, the possibility that yet unidentified subsets of parameters are responsive to placebo treatments has not been taken into account. Therefore, the aim of the present study is to examine the effects of placebo treatments on objectively measured outcome parameters by specifically focusing on peripheral disease process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 85 publications
1
52
0
4
Order By: Relevance
“…For example, one could conclude that those who participate more are more likely to perceive a positive effect on their well-being; this could be interpreted as a form of placebo effect. Yet it has been widely demonstrated that such effects work in improving overall well-being (Beauregard, 2007;Koshi & Short, 2007;Meissner, Distel, & Mitzdorf, 2007), and it does seem clear that this is the case with CE membership as well. Because many people who join time banks are older and experiencing health problems, it would not be surprising to see some decline in health over time, especially among older members who have been members for several years.…”
Section: Limitationsmentioning
confidence: 99%
“…For example, one could conclude that those who participate more are more likely to perceive a positive effect on their well-being; this could be interpreted as a form of placebo effect. Yet it has been widely demonstrated that such effects work in improving overall well-being (Beauregard, 2007;Koshi & Short, 2007;Meissner, Distel, & Mitzdorf, 2007), and it does seem clear that this is the case with CE membership as well. Because many people who join time banks are older and experiencing health problems, it would not be surprising to see some decline in health over time, especially among older members who have been members for several years.…”
Section: Limitationsmentioning
confidence: 99%
“…While placebo has clinical benefits, it has not been shown to have specific effects in terms of biologic markers. [20][21][22][23] There are some intriguing findings in this study even as a single case study. The lengthy RNG control sessions in nontherapeutic settings such as a business office had Z scores of 0.03, as expected, with no trials having a Z score > 2.…”
Section: Discussionmentioning
confidence: 69%
“…Such a response is defined as 'the psychobiological response seen after administration of a non-therapeutic modality'. Placebo treatments have known effects on endogenous pharmacology, as well as the cognitive and conditioning systems in humans [312][313][314][315][316][317][318][319]. The placebo response rate is higher in children compared with adults [320,321].…”
Section: The Mechanism and Effects Of Ivlt In Chronic Painmentioning
confidence: 99%